Diverse Presentations of Carcinoma Erysipelatoides from a Teaching Hospital in Australia. (23rd December 2012) - Chow, Hui Ting; Tran, Kim; Millar, Ewan K. A.; Lynch, Jodi; Murrell, Dedee F.
Abstract : Inflammatory breast carcinoma is a rare form of advanced breast cancer which carries a poor prognosis, even with treatment. Diagnosis is reached on clinical and pathological grounds; however, due to its propensity to mimic other conditions, it may often be delayed or missed by attending physicians. This case series describes four patients seen at our institution with a diagnosis of inflammatory breast cancer; 3 patients had a history of previously treated breast malignancy. In these cases, the emergence of a new breast lesion evaded initial diagnosis due to incomplete initial physical examination, falsely reassuring imaging results, lack of recognition that a cellulitis picture can resemble metastatic carcinoma, and inconclusive initial biopsy sections. These obstacles to achieve diagnosis serve to further worsen the prognosis by delaying the initiation of multimodality treatment which can improve survival. The purpose of our paper is to increase awareness among breast cancer specialists of the importance of undressing the patient for basic clinical examination of the breasts, recognition of the appearances of this type of local recurrence of breast cancer, and not to rely purely on ultrasound and mammography due to delay in diagnosis in some of our local cases. Sometimes deeper sections and repeat biopsies are needed to make the diagnosis.